MENUMBUHKAN JIWA ENTREPRENEUR UNTUK MENINGKATKAN PENDAPATAN PADA ANGGOTA RUMAH BACA JAKOSE MELALUI BISNIS MODEL CANVAS (BMC) (Jurnal Pengabdian Masyarakat UNAMA, 2023)
The importance of resources, especially financial, in social organizations is especially felt by one of the social organizations, namely the jakose reading house (Jambi Kota opposite) where in carrying out activities there must be funds that must be spent so that activities run smoothly. Therefore, with this training it is hoped that the members of the jakose reading house can increase their entrepreneurial spirit and express and create their business ideas through the Canva business model, which is related to easy use, it is hoped that the members of the jakose reading house will be able to so businesses that provide income for their operations or social activities will later be generated through training "growing an entrepreneurial spirit to increase income for members of the jakose reading house through the Business Model Canvas (BMC)" The Jakose Reading House (Jambi Kota Bawah) itself is a social organization which wants to make the Jakose Reading House a forum for channeling creativity according to talents and interests for teenagers and the community. And it has a mission to instill the habit of reading and learning into an interesting hobby and activity. for children in realizing the abilities of children who understand creative and intelligent moral values so that they can take roles for society and the environment The method used in this activity is training with the following steps 1) Providing an understanding of entrepreneurs, to the jakose member group, 2) Theory simulation, in the form of practicing using the Business Model Canvas (BMC), 4) Monitoring for 1 month, 5) Evaluation.